A Decade of World Bank Support to Senegal’s Nutrition Program : Analysis and Perspective - 15 Years of Experience in the Development of Nutrition Policy in Senegal - Vaillancourt, Denise (World Bank, Washington, DC, 2018)
At the start of the new millennium, malnutrition in Senegal was of great concern. Among children under five years of age almost one-third (30 percent) were stunted (low height for age), 10 percent were wasted (low weight for height), and 20 percent were underweight (weight for age), each of these levels categorized as high severity by the World Health Organization (WHO). Rates vary greatly, with the poor and rural, and residents of the north, south and central zones, suffering disproportionately. Malnutrition contributes to child and maternal mortality and morbidity, undermines children’s prospects of reaching their physical and intellectual potential, and undercuts income-earning potential for households and overall productivity and economic development. Its two principal causes are inadequate food intake and illness. In 2001, the government of Senegal issued a new nutrition policy, supporting a 10-year goal to improve nutrition through a community-based, multisectoral approach. The policy was translated into the 10-year Nutrition Enhancement Program (NEP), financed by the government of Senegal, the World Bank, and eventually others. This report assesses the performance of three projects: (1) the NEP, (2) the Nutrition enhancement project in support of the second phase of the NEP, and (3) the Rapid response child-focused social cash transfer and nutrition security project